Maximum mass of axisymmetric rotating quark stars. Issue 9 (28th November 2017) - Zhou, E.; Tsokaros, A.; Rezzolla, L.; Xu, R.
Abstract : The internal structure of pulsar‐like compact stars is still a puzzle, as the equation of state (EoS) of cold dense matter is unclear yet. One way to distinguish between different EoSs of compact stars is based on the maximum mass of different EoSs, which can be estimated by solving the Tolman–Oppenheimer–Volkoff (TOV) equation. In a more realistic consideration, rotations should to be taken into account when estimating the maximum mass. It has been shown that rotating neutron stars could support up to 20% more mass compared with the TOV maximum mass ( M TOV ). However, apart from neutron star models, other models such as the quark star or the hybrid star model are also suggested as possible EoSs for compact stars. In this work, we apply numerical relativity calculation for axisymmetric rotating quark stars and investigate the solution sequences. We consider both the conventional MIT Bag model and another stiff EoS (strangeon star model) in our calculations. We find that rotating quark stars, different from rotating neutron stars, can support up to roughly 40% more mass than M TOV . Possible astrophysical influence and possible ways to distinguish between EoSs are discussed.